2017
DOI: 10.1097/rlu.0000000000001650
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of an Acrochordon Incidentally Detected on 68Ga Prostate-Specific Membrane Antigen PET/CT

Abstract: Ga prostate-specific membrane antigen (PSMA) PET/CT is a promising tool for imaging of prostate cancer. Ga-PSMA PET/CT uptake of prostate cancer and its metastases are reflective of significant overexpression of PSMA. However, PSMA expression of benign neoplasms and nonprostate epithelial malignancies is not very well defined. We report a moderate Ga-PSMA uptake of an acrochordon (skin tag), which was incidentally found in a patient referred for staging prostate cancer. Acrochordon is a frequent, small, soft, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Increased 68 Ga-PSMA uptake can be seen in many cancers such as renal cell carcinoma, primary lung, breast, and thyroid, and in benign conditions such as sarcoidosis, tuberculosis, adrenal adenoma, and schwannoma. Increased 68 Ga-PSMA has been reported in skin lesions; malignant melanoma, dermatofibroma, acrochordon, angiofibroma, and neurofibroma as in our case 3–6 . Neurofibroma consists of Schwann cells, fibroblasts, mast cells, macrophages, and other neuronal structures, and it is the most common benign tumor originating from the peripheral nerve sheath 7 .…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Increased 68 Ga-PSMA uptake can be seen in many cancers such as renal cell carcinoma, primary lung, breast, and thyroid, and in benign conditions such as sarcoidosis, tuberculosis, adrenal adenoma, and schwannoma. Increased 68 Ga-PSMA has been reported in skin lesions; malignant melanoma, dermatofibroma, acrochordon, angiofibroma, and neurofibroma as in our case 3–6 . Neurofibroma consists of Schwann cells, fibroblasts, mast cells, macrophages, and other neuronal structures, and it is the most common benign tumor originating from the peripheral nerve sheath 7 .…”
supporting
confidence: 58%
“…Increased 68 Ga-PSMA has been reported in skin lesions; malignant melanoma, dermatofibroma, acrochordon, angiofibroma, and neurofibroma as in our case. [3][4][5][6] Neurofibroma consists of Schwann cells, fibroblasts, mast cells, macrophages, and other neuronal structures, and it is the most common benign tumor originating from the peripheral nerve sheath. 7 Increased capillary permeability is a possible mechanism of 68 Ga-PSMA uptake because neurofibroma also shows increased uptake for 67 Ga-citrate, 99m Tc-DTPA, 99m Tc-MDP, 201 Tl and, 131 I. Cross-reactivity with unknown antigens in the lesion is another hypothesis for radiopharmaceutical uptake.…”
mentioning
confidence: 99%
“…An 84-year-old man with a newly diagnosed prostate adenocarcinoma was referred to 18 F-prostate-specific membrane antigen (PSMA) PET/CT for initial staging. A, MIP image of whole-body 18 F-PSMA PET/CT study showed intense focal PSMA uptake in the prostate gland consistent with the primary tumor (white arrowhead). PET/CT also demonstrated increased PSMA uptake in the medial aspect of the proximal right thigh (arrow).…”
mentioning
confidence: 99%
“…3 The avidity in some of these cases has been ascribed to the PSMA expression in the endothelial cells of the tumor neovasculature. 4 A few more case reports showing nonmalignant causes of PSMA uptake in nonneoplastic processes [5][6][7][8][9][10][11][12][13] and in benign neoplasms [14][15][16][17][18][19][20][21][22][23] are reported in the literature. Spindle cell lipoma is a rare variant of lipoma, characterized by mature adipocytes and small uniform spindle cells.…”
mentioning
confidence: 99%
“…Benign neoplasms and diseases, for example, include schwannoma, 4,5 thyroid adenoma, 6 sarcoidosis, 7 as well as Paget disease of the bone, 8 whereas malignant lesions exemplarily include renal cell carcinoma, 9 colon carcinoma, 10,11 and breast cancer 12,13 . Moreover, a variety of cutaneous lesions with increased PSMA expression such as angiolipoma, 14 dermatofibroma, 15 subcutaneous lobular capillary hemangioma, 16 and acrochordons 17 are described in the literature. This present case adds 1 additional, hitherto undescribed, benign cutaneous lesion (epidermoid cyst) that should be taken into consideration when evaluating PSMA-ligand uptake in lesions of unknown classification.…”
mentioning
confidence: 99%